ONOMATOPE DALAM WEBTOON SI JUKI: LIKA LIKU ANAK KOST KARYA FAZA MEONK - Khairunisa Khairunisa Khairunisa; Tri Yuliawan (Jurnal Suluh Pendidikan, 2026)
This study aims to examine the function and contextual meaning of onomatopoeia used in the Webtoon Si Juki: Lika Liku Anak Kost. This study applies a descriptive qualitative approach based on semantic studies. The data sources come from 51 episodes of the Webtoon, namely episodes 0 to 50, with a focus on linguistic units in the form of onomatopoeia that appear in visual narratives. Data collection was carried out through documentation techniques, then analyzed using the Miles and Huberman interactive analysis model, which includes data reduction, data presentation, and drawing conclusions. The analysis is based on the theory of onomatopoeia functions of Thomas & Clara (2004) and the concept of contextual meaning of Chaer (2014). The results of the study identified 176 onomatopoeia data spread across four function categories, namely giving a strong impression to the reader (127 data), enriching information in the text (36 data), building rhythm or musicality of sound (7 data), and strengthening the impression of the reality of events (6 data). These findings indicate that the use of onomatopoeia in Webtoon is more dominant as a reinforcement of expression and dramatic intensity, especially in building humor and surprise effects. In terms of meaning, onomatopoeia cannot be understood solely based on its lexical meaning, but must be interpreted through the visual context, story situation, and interactions between characters in a multimodal narrative structure. Thus, this research contributes to the development of contextual semantics and multimodal linguistic studies, particularly in understanding the function of onomatopoeia as an important semiotic element in digital comics.